2020
DOI: 10.1039/c9ta09401f
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of computational methods for the electrochemical stability window of solid-state electrolyte materials

Abstract: Superior stability and safety are key promises attributed to all-solid-state batteries (ASSBs) containing solid-state electrolyte (SSE) compared to their conventional counterparts utilizing liquid electrolyte. To unleash the full potential of ASSBs, SSE materials that are stable when in contact with the low and high potential electrodes are required. The electrochemical stability window is conveniently used to assess the SSE-electrode interface stability. In the present work, we review the most important metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
85
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 66 publications
(93 reference statements)
2
85
0
Order By: Relevance
“…In addition, Binninger et al [276] performed computational studies on the electrochemical stability voltage window of these electrolytes. (iii) The experimental observations were further validated by the results of the computational study performed by Jay et al [472].…”
Section: Perovskite-type Structure Electrolytesmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, Binninger et al [276] performed computational studies on the electrochemical stability voltage window of these electrolytes. (iii) The experimental observations were further validated by the results of the computational study performed by Jay et al [472].…”
Section: Perovskite-type Structure Electrolytesmentioning
confidence: 99%
“…Computational studies offered further insight into the size of the bottleneck and indicated a possible increased using large rare-earth or alkaline-earth metal ions as A-site ions; moreover, changing the bond strength between the B-site cations and O also affects the conductivity of these electrolytes. In addition, Binninger et al [276] performed computational studies on the electrochemical stability voltage window of these electrolytes.…”
Section: Perovskite-type Structure Electrolytesmentioning
confidence: 99%
See 3 more Smart Citations